REPRODUCTIVE CYCLE AND BIOCHEMICAL CHANGES IN THE GONADS OF THE FRESHWATER CRAB, BARYTELPHUSA CUNICULARIS (WESTWOOD, 1836) - Diwan, A D; Nagabhushanam, R (Indian Journal of Fisheries, 2011)
The annual breeding cycle of the crab, Barytelphusa cunicularis, was determinedby measuring monthly the size of the gpnad relative to the size of theanimal. The peak of gonad size appeared in rainy season (June to September)showing the maximum breeding activity during these months. Histological observationsof the monthly gonads revealed that the ripening of the gonads startedduring March and extended upto May. By June the gonads of most of theindividuals attained full maturity and spawning began. Spawning terminated bythe end of September and the gonads entered a quiescent period.Monthly changes in the boichemical constituents of gonads were studiedfor one year to determine their variability in the course of the reproductive cycle.During the ripening of the gonads, glycogen, fat and protein contents were high.During spawning period all values fell considerably reaching the minimum valuesat the end of spawning season. During the maturation of the gonads glycogen,fat and protein contents were increased